Answer:
d) x = 2
Step-by-step explanation:
3(x - 6) + 3 = -9
<em>open the parenthesis</em>
3x - 18 + 3 = -9
3x - 15 = -9
<em>add 15 to both sides of the equation</em>
3x - 15 + 15 = - 9 + 15
3x = -9 + 15
3x = 6
<em>divide both sides by 3</em>
3x/3 = 6/3
x = 6/3
x = 2
1.75
2.15
3.105
4.90
these are the answers
Wait where’s the question?
Let's solve your equation step-by-step.
2
x
=
12
Step 1: Divide both sides by 2.
2
x
2
=
12
2
x
=
6
Answer:
x
=
6
Answer:
The leading coefficients of f(x) and g(x) are opposites.